The effect of late foliar application on rice grain production / Hafizzudin Abd Karim - Abd Karim, Hafizzudin (Faculty of Plantation and Agrotechnology, 2019)
Low production in rice sector was one of besetting problem in Malaysia. As the demand of the rice is continuously increasing especially in Asian region, production of rice should also be increased. A study was conducted to see the effect of late foliar application on the grain production of rice. By applying the foliar fertilizer during later stage of rice growth, the nutrient can be directly absorbed by the rice for grain production, instead of vegetative development. This study conducted in greenhouse located at UiTM Jasin by using Randomized Control Block Design (RCBD). The treatments were application of different dosage of foliar fertilizer in two varieties of rice, MR 219 and MR 269 to see the effectiveness in improving grain production. Treatment one act as control with 0% of foliar application, treatment 2 with 50% of foliar application, treatment 3 with 100% and treatment 4 with 150% dosage. SPAD, height, grain, panicle, straw and biomass were measured during the study. Plant height, SPAD, panicle, straw, did not showed any significant difference among the treatment but result in grain, 100 grain, and straw show significant difference between the treatment. Applying foliar fertilizer in treatment 2, 3 and 4, there was a different in total weight comparing with treatment 1. Result also showed weight in 100 grain between treatment is different. There was higher 100 grain in treatment 4 comparing with other.